Electron microscopic study of crystals of the Xenopus laevis transcription factor IIIA-5S ribosomal RNA complex. - Brown, R S (1988)
A novel method has been developed to grow crystals of the Xenopus laevis transcription factor IIIA-5S RNA complex directly on grids for examination by electron microscopy. Microcrystals were examined in negative stain and in thin sections to reveal a hexagonal lattice with unit-cell dimensions a = b = 87.1 +/- 4.4 A and c = 143.8 +/- 12.7 A. Optical diffraction patterns from micrographs were obtained about the major crystal axes extending to about 40-A resolution. A packing scheme is proposed for which there are three or six transcription factor IIIA-5S RNA complexes in the unit cell related by 3(1) symmetry along the long cell axis. This would require that the 5S RNA molecules are arranged end-to-end, with the terminal loops of adjacent molecules overlapping.